Children disengaged from armed groups in Colombia. Integration Processes in Context - Villanueva O'Driscoll, Julia (De Gruyter, 2013)
An in-depth study of the complex situation in Colombia; extensive research involving a broad range of participants. Drawing on a broad research on historical, geographical and socio-political context of the Colombian conflict, the book explores the role of children entangled in the military fighting. Following the case studies of minors, starting from the recruitment up to the disengagement, the authors seek to understand the process itself and to analyze various support methods offered to the affected children. Weaving together different points of view, coming from the children, and from the workers of the organizations offering help, the book gives an engaging and dramatic overview of the phenomenon of child soldiers.